(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The article discusses present condition of the state control in the european socialist countries also taking into account the more general issues of the evolu- tion of this institution in the socialist constitutionalism. The research material was gathered into four main classification groups considering the position of the organs of control in the structure of state apparatus: a) the party and state control — now in the GDR; b) control situated near the central representative organs — now in Rumania, Bulgaria and the USSR; c) control functioning as a government department of state administration — now in Czechoslovakia, Hungary and Poland; d) control functioning in the form of a specificly created chamb- er situated beyond the state apparatus — in Yugoslavia. The above classifica- tion allows us at the same time to point out the principal tendencies in placing the organs of control in the structure of the state apparatus, e.g. in Bulgaria where state control was first functioning as a government department later reor- ganized into party and state control system and beginning with 1974 placed near the central representative organs. Thus, while discussing specific’ classification group the Author tried to present the evolution of the system of control in a particular country. The Author developed also a wider issue of connections in between state and party control, highly specialized control of the government departments as well as social supervision in each discussed country. The final part of the article tends to present more general common tendencies charaterizing socialist control regardless of its position in the structure of the state apparatus. In particular, the following issues were stressed: the role of state control in safeguarding the rule of law; involving the working people into the management of the state by way of participation in the organs of social supervision; connections in between state control and party control and their mutual inspirations; the influence of science on further improvement of the socialist control.